Case studies in comparative politics - Samuels, David J.
Debuting in its first edition and written by a new generation of area studies experts, Case Studies in Comparative Politics follows a questions-based approach that helps readers understand different countries' political histories, institutions, identities, and interests and why each country is politically interesting and relevant. When used on its own or with the accompanying thematic survey, Case Studies in Comparative Politics asks-and answers-the same important questions that political scientists research and that are relevant to anyone interested in politics.